Dampak Penerapan Kebijakan Free Trade Zone di Indonesia Terhadap Penanaman Modal Asing - Puri Diah Santyarini; Maddaremmeng A. Panennungi (Universitas Diponegoro, Indonesia, 2021)
Economic zones are always considered to be a strategy for a country to attract FDI, including Indonesia that has designated several regions as FTZ, namely Sabang and Batam (2000) also Bintan and Karimun (2007). Therefore, this study tries to see the impact of FTZ policies on the entry of FDI in Indonesia. Using fixed effect panel data method for the period 1999-2018 and focusing on policies, characteristics, and socioeconomic conditions of FTZ in Indonesia. It shows that the FTZ has positive impact on increasing FDI in Indonesia only if the region has socioeconomic characteristics and conditions that are stable and supportive toward investment climate